"Strange" particles and micro-sized ball lightning in some electric discharges. (July 2021) - Nikitin, Anatoly I.; Nikitin, Vadim A.; Velichko, Alexander M.; Nikitina, Tamara F.
Abstract: When conducting experiments on the electric explosion of titanium foil in water, a "strange" radiation was detected, leaving dotted traces on the film. The velocity of the carriers of this radiation was estimated as 20–40 m/s, and their energy, estimated by the Coulomb drag mechanism, turned out to be equal to 700 MeV. Subsequently, it was found that similar traces are formed at various types of high-current arc discharges, both of artificial and natural origin. Many solutions have been proposed to explain the nature of "strange" radiation, but none of them describes the details of the process of formation of dotted traces. We believe that these traces on the film could appear due to the action of charged micron-sized clusters. The possibility of the existence of clusters in the form of a nucleus from a certain number of similarly charged ions enclosed in a spherical shell of water molecules is shown. The force of the Coulomb repulsion of ions is compensated by the compression force of the shell polarized by the inhomogeneous electric field created by the nuclear charge. As the cluster approaches the surface of the film, a cluster with a small charge separates from it. It is accelerated in the electric field of a "large" cluster to energy of about 1 GeV. Having received a recoil momentum, a large cluster moves away from the film, braking in an inhomogeneous electric field, and then "falls" onto it again, and the process is repeated. Highlights: During electric discharges in media, dotted traces appear on photographic films. The existence of charged clusters – micro-sized ball lightning is possible. These clusters emit charges in the direction of the film and are repelled from the film. Charged clusters are formed during the flow of strong currents through materials.